10+10ae^(-b*15)=70

10ae^(-b*15)=60

a=60/(10e^(-b*15))

a(10e^(-b*15))=60

10ae^(-b*15)=60

ae^(-15b)=6

log(ae^(-15b))=log(6)

log(a)-15b*log(e)=log(6)

-15b*log(e)=-log(a)+log(6)

b=(log(a)-log(6))/(15log(e))

b=(log(60/(10e^(-b*15)))-log(6))/(15log(e))

b=(log(60/(10e^(-b*15)))-0.7781512504)/(6.514417229)

b=(log(6(1e^15b))-0.7781512504)/(6.514417229)

b=(log(16.30969097^15b)-0.7781512504)/(6.514417229)

6.514417229b=log(16.30969097^15b)-0.7781512504

7.292568479=log(16.30969097^15b)

10^7.292568479=16.30969097^15b

19614104.26=16.30969097^15b

log(base 16.30969097)19614104.26=15b

6.01475867=15b

b=0.4009839113

a=60/(10e^(-b*15))

a=60/(10e^(-0.4009839113*15))

a=60/10e^-6.01475867

a=2456.562119

t(x)=70/(1+2456.562119e^(-0.4009839113x))

Unfortunately, when I tested a point, it was wrong.

What did I do incorrectly?